2018
DOI: 10.1016/j.advwatres.2017.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of the effects of contact angle and viscosity ratio on the dynamics of snap-off through porous media

Abstract: Snap-off is a pore-scale mechanism occurring in porous media in which a bubble of nonwetting phase displacing a wetting phase, and vice-versa, can break-up into ganglia when passing through a constriction. This mechanism is very important in foam generation processes, enhanced oil recovery techniques and capillary trapping of CO 2 during its geological storage. In the present study, the effects of contact angle and viscosity ratio on the dynamics of snap-off are examined by simulating drainage in a single pore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Since the effect of preferential flow will be remarkable in leading the non-equilibrium fluid flow subsurface, accurate knowledge and description the preferential paths and interfacial dynamic of immiscible two-phase flow in rock mass and its influence factors are of great significance for the evaluation of oil or gas recovery 1,2 and predication of roadway rock disasters 3 due to the gas-liquid flow. Many studies have been conducted to analyze preferential flow in order to explore the influence factors including wettability 46 , capillary pressure 7,8 , injection rate 9 , viscosity ratio 6 and capillary number 10 . However, few experimental and numerical studies are available for quantitatively and visually elaborating the fundamental processes of preferential flow in real rock structures through the effect of pore morphology and channel size, due to the complexity and heterogeneity of porous structures of natural rocks.…”
Section: Introductionmentioning
confidence: 99%
“…Since the effect of preferential flow will be remarkable in leading the non-equilibrium fluid flow subsurface, accurate knowledge and description the preferential paths and interfacial dynamic of immiscible two-phase flow in rock mass and its influence factors are of great significance for the evaluation of oil or gas recovery 1,2 and predication of roadway rock disasters 3 due to the gas-liquid flow. Many studies have been conducted to analyze preferential flow in order to explore the influence factors including wettability 46 , capillary pressure 7,8 , injection rate 9 , viscosity ratio 6 and capillary number 10 . However, few experimental and numerical studies are available for quantitatively and visually elaborating the fundamental processes of preferential flow in real rock structures through the effect of pore morphology and channel size, due to the complexity and heterogeneity of porous structures of natural rocks.…”
Section: Introductionmentioning
confidence: 99%
“…Roof 12 theoretically analyzed the droplet breakup in a microconstriction under the assumption that the oil droplet moved at a negligible velocity (i.e., quasistatic breakup), and concluded that the droplet breakup occurred in a microconstriction when the capillary pressure of the droplet head was equal to that of the neck. This conclusion was widely verified at extremely low droplet velocity and laid a foundation for the research on droplet breakup in more complicated constrictions 13–19 . However, Roof's 12 breakup criterion was not applicable in a larger range of droplet velocity.…”
Section: Introductionmentioning
confidence: 93%
“…This conclusion was widely verified at extremely low droplet velocity and laid a foundation for the research on droplet breakup in more complicated constrictions. [13][14][15][16][17][18][19] However, Roof's 12 breakup criterion was not applicable in a larger range of droplet velocity. Wang et al 20 and Liang et al 21 experimentally investigated the breakup of the droplet flowing through a locally constrictive microchannel at a nonignorable velocity (i.e., dynamic breakup), concluding that the daughter droplet size was underestimated based on Roof's 12 theory.…”
Section: Introductionmentioning
confidence: 99%
“…For the sake of simplicity, the viscosity ratio is taken equal to 1. A numerical study on the effects of viscosity ratio on the two-phase flow dynamics in constricted pore-throat geometries can be found in Starnoni and Pokrajac (2018). Boundary conditions consist of prescribed pressure at the outlet and velocity equal to 5 mm/s at the inlet.…”
Section: Numerical Setupmentioning
confidence: 99%